2017
DOI: 10.1080/17425247.2017.1316262
|View full text |Cite
|
Sign up to set email alerts
|

The effects of particle size, shape, density and flow characteristics on particle margination to vascular walls in cardiovascular diseases

Abstract: Introduction: Vascular-targeted drug delivery is a promising approach for the treatment of atherosclerosis, due to the vast involvement of endothelium in the initiation and growth of plaque, a characteristic of atherosclerosis. One of the major challenges in carrier design for targeting cardiovascular diseases (CVD) is that carriers must be able to navigate the circulation system and efficiently marginate to the endothelium in order to interact with the target receptors. Areas covered: This review draws on stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 108 publications
2
59
0
Order By: Relevance
“…Spherical shaped or spheres are ease to synthesis and have been studied for years. They are quickly up taken by microphages and stay for shorter time in circulation as compared to non-spherical nanoparticles [25,26]. However, the sizes observed also correlated well with the hydrodynamic diameters measured by the Zetasizer (Figure 4).…”
Section: Characterization Of Pcl Nanoparticles and Liposomessupporting
confidence: 75%
“…Spherical shaped or spheres are ease to synthesis and have been studied for years. They are quickly up taken by microphages and stay for shorter time in circulation as compared to non-spherical nanoparticles [25,26]. However, the sizes observed also correlated well with the hydrodynamic diameters measured by the Zetasizer (Figure 4).…”
Section: Characterization Of Pcl Nanoparticles and Liposomessupporting
confidence: 75%
“…Confocal microscopy images in Figure showed that large nanoparticles (130 nm) associated with HUVECs to a greater extent than medium and small particles (70 and 40 nm), which is consistent with data obtained by flow cytometry (Figure ). It has been shown that large nanoparticles exhibit a higher tendency to tumble out of the general circulation and scavenge along vascular walls than smaller nanomaterials . This tendency may increase the exposure of large nanoparticles with TA‐tagged groups to endothelial cells and as a result, increase cellular association.…”
Section: Resultsmentioning
confidence: 99%
“…For the above clinical applications, nanomaterials circulate in the human vascular network before reaching their targets (e.g., cancer cells, immune cells, or blood clots) . As such, investigating and understanding the complex nano–bio interactions between nanomaterials and biological systems inside vascular networks (e.g., endothelial cell adhesion) are critical for designing nanoparticles with desired properties for these applications . For instance, nanoparticles carrying anticancer drugs are expected to have a minimal off‐target association with healthy endothelial cells before reaching tumors .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the size and shape of nanoparticles are crucial factors that impact their properties and applications . For instance, the size and shape of PISA nanoparticles have been found to significantly affect their in vivo biodistribution .…”
Section: Introductionmentioning
confidence: 99%